Isolated Talonavicular Arthrodesis as Treatment for Flexible Progressive Collapsing Foot Deformity: A Case Series - Fernando C. Raduan MD; Hui Zhang MD; Bryan D. Den Hartog MD; J. Chris Coetzee MD; Jeffrey D. Seybold MD; William M. Engasser MD; Rebecca Stone McGaver MS; Jacquelyn E. Fritz BS; Kayla Seiffert BA; Marc Giveans (Foot & Ankle Orthopaedics, 2022)
Category: Hindfoot; Other Introduction/Purpose: Progressive collapsing foot deformity (PCFD) remains a challenging condition for foot and ankle surgeons to treat. While there exists more clarity on the treatment for end-stage rigid deformities involving PCFD, there is still significant debate over different surgical treatment options for the flexible collapsing foot. Common surgical corrections for flexible PCFD include the 'All-American Procedure' popularized by Manoli in the 1990s. Isolated talonavicular (TN) arthrodesis has also been described for the treatment of flexible PCFD. The primary objective of this study was to evaluate clinical and radiographic outcomes in patients with AAFD treated with isolated tri-planar corrective TN arthrodesis. A secondary objective was to establish whether there is a correlation between radiographic outcomes and clinical outcomes. Methods: Fifty-four patients (59 feet) from July 2013 to October 2020 with flexible PCFD underwent surgical treatment with isolated TN arthrodesis. Patients with other arthrodesis or hindfoot osteotomies were excluded. Concomitant gastrocnemius lengthening and toe deformity correction procedures were not an exclusion criterion. Weight-bearing radiographs were performed pre- and postoperatively, with Meary angle (or lateral talo-first metatarsal angle) and calcaneal pitch measured on lateral view. The degree of TN coverage on antero-posterior (AP) radiographs were measured with the TN coverage angle and the degree of first ray angular deformity was measured using Simmon angle (or AP talo-first metatarsal angle). Angles were measured by a foot and ankle fellow. The Foot & Ankle Ability Measure (FAAM) and Veterans-Rand 12 Item Health Survey (VR- 12) were used to clinically evaluate the patient. Results: Thirty-seven females and seventeen males were evaluated with a mean age 61 years at the time of surgery and an average length of follow up of 19 months. There were significant improvements in deformity correction found in this study. Radiographically, the lateral radiographs demonstrated Meary angle correction from 27 degrees pre-operatively to 9 degrees post- operatively (p<0.001) and calcaneal pitch improving from 15 degrees pre-operatively to 18 degrees post operatively (p<.001). AP radiographic analysis demonstrated TN coverage angle improving from 35 degrees pre-operatively to 5 degrees post-operatively (p<0.001) and Simmon angle improving from 20 degrees pre-operatively to 6 degrees, post-operatively (p<.001). The only statistically significant improvement in clinical outcomes was in the FAAM score (pre-operative score 48.48, post-operative score 58.45 (p<.001)). Conclusion: Isolated TN arthrodesis is a viable option for multi-planar deformity correction in patients with flexible PCFD. Not only did it provide significant improvements in radiographic alignment, it also provided improved functional outcomes as demonstrated on FAAM scores. Comparative studies with other surgical treatment techniques such as the 'All-American Procedure' should be performed to determine which is the best technique for patients with flexible PCFD.